Actor Interactions for Circular Economy Implementation in Rural–Urban Interfaces: Evidence from Malang Regency - Munda Rahma Dana; Rizky Renuka Avelia; Imam Mukhlis (Efficient: Indonesian Journal of Development Economics, 2026)
This study aims to analyze the role of collaboration between actors in achieving sustainable development goals through the implementation of a circular economy in Karangwidoro Village, Malang Regency, East Java, Indonesia. Malang Regency was chosen because it has representative peri-urban characteristics, with rapid urbanization and coexistence between urban and rural elements. The data used are primary data through in-depth interviews and direct observation. Data collection was carried out from February to March 2025. This study uses MACTOR (Matrix of Alliances and Conflicts, Tactics, and Objectives for Risk Analysis) analysis to analyze among 9 main stakeholders, such as managers, partners, government officials, academics, and local communities. The research findings show that strong collaboration between central actors such as local governments, program managers, and academic institutions is critical to the successful implementation of a circular economy. However, challenges remain, especially with peripheral actors such as local communities, whose involvement tends to be sporadic and dependent on external factors. This study concludes that to ensure the sustainability of the program, collaboration between various existing actors is very important in achieving sustainable development goals through a circular economy, by utilizing synergies between government, society, private sector, and academics.